A method for assembling and testing polysulfide flow battery based on membrane electrode
Patent Information
- Application Number
- CN202210460656.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-28
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-04-28
AI Technical Summary
Due to the slow redox kinetics and severe membrane penetration effect, polysulfide flow batteries have low output power, poor Coulomb efficiency and circulation performance, and cannot achieve large-scale industrial applications.
The first catalyst layer is scraped on the negative electrode of the polysulfide flow cell, and the second catalyst layer is sprayed on the side near the negative electrode on the cation exchange membrane, using graphene-supported transition metal sulfide or transition metal-nitrogen-carbon As a catalyst, the material improves the distribution area and utilization rate of the catalyst and inhibits the film penetration effect of polysulfides.
It significantly improves the polysulfide redox kinetics and battery power density, improves Coulomb efficiency and cycling performance, and enhances the stability and application potential of the battery.
Smart Images

Figure CN114759236B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polysulfide liquid flow battery based on a membrane electrode and a preparation method thereof, belonging to the technical field of liquid flow batteries. Background Art
[0002] Liquid flow battery is a high-performance battery in which the positive and (or) negative electrolyte solutions are stored in a tank outside the battery and transported to the inside of the battery through pumps and pipelines for reaction. Inside the battery, the positive and negative electrolytes are separated by an ion exchange membrane (or ion diaphragm), and the positive and negative electrolytes are separated and circulated separately. Unlike ordinary secondary batteries, the energy storage active material of the liquid flow battery is completely separated from the electrode, and the power and capacity design are independent of each other, which is easy to combine modules and place the battery structure; the electrode only provides a place for electrochemical reaction and does not undergo redox reaction itself; the active material is dissolved in the electrolyte, and the risk of electrode dendrite growth piercing the diaphragm is greatly reduced in the liquid flow battery; at the same time, the flowing electrolyte can take away the heat generated by the battery charging / discharging process, avoiding damage to the battery structure or even combustion caused by battery heating. Liquid flow batteries have the characteristics of high capacity, wide application field (environment), and long cycle life, and have broad application prospects.
[0003] Polysulfides are the most promising negative electrode active materials for building high energy density liquid flow batteries due to their advantages such as multiple electrons, high solubility and low cost. However, due to the sluggish redox kinetics of polysulfides, the output power of the battery is low; due to the non-conductive elemental sulfur deposited on the membrane and the positive current collector (membrane penetration effect) produced by polysulfides, the coulombic efficiency and cycle performance of the battery are poor. Due to the above shortcomings, large-scale industrial application of polysulfide liquid flow batteries cannot be achieved at present. Summary of the invention
[0004] The present invention provides an assembly and testing method for a polysulfide flow battery based on a membrane electrode, which can effectively solve the above problems.
[0005] The present invention is achieved in that:
[0006] A polysulfide flow battery based on a membrane electrode has a first catalyst layer scraped onto the negative electrode of the battery and a second catalyst layer sprayed onto one side of the cation exchange membrane of the battery close to the negative electrode.
[0007] As a further improvement, the catalyst materials of the first catalyst layer and the second catalyst layer are transition metal sulfides or transition metal-nitrogen-carbon materials supported by graphene.
[0008] As a further improvement, the transition metal sulfide supported by graphene is selected from CoS x @rGO、CuS x@rGO、Ni3S4@rGO、Ni 1-x Co x S2@rGO、Ni 3-x Co x One or more of S4@rGO.
[0009] As a further improvement, the transition metal-nitrogen-carbon material is selected from one or more of Fe-NC, Co-NC, and Ni-NC.
[0010] As a further improvement, the catalyst loading of the first catalyst layer is 2-30 mg / cm 2 The catalyst loading of the second catalyst layer is 1-20 mg / cm 2 .
[0011] A method for assembling the above-mentioned polysulfide flow battery based on membrane electrode comprises the following steps:
[0012] S1, preparing the catalyst material into a scraping slurry, and scraping it on the surface of the negative electrode;
[0013] S2, preparing the catalyst material into a spray slurry, and spraying it on the surface of the cation exchange membrane;
[0014] S3, assembling the polysulfide flow battery, ensuring that the side of the cation exchange membrane sprayed with the catalyst faces the negative electrode.
[0015] As a further improvement, the catalyst material is prepared into a scraping slurry or a spraying slurry by uniformly dispersing the catalyst material in an organic solvent A, dissolving a binder in an organic solvent B, mixing the two solutions, and ultrasonically dispersing to obtain a scraping slurry or a spraying slurry.
[0016] As a further improvement, the organic solvent A is selected from one or more of ethanol, isopropanol or n-propanol; the organic solvent B is selected from one or more of N,N-dimethylformamide or N-methylpyrrolidone; and the binder is selected from one or more of PVDF, PTFE and Nafion.
[0017] As a further improvement, the mass ratio of the catalyst material to the binder is 20:1-2:1.
[0018] As a further improvement, the sprayed cation exchange membrane is hot pressed at 80°C-200°C and 0.1-10 MPa for 1-20 min.
[0019] The beneficial effects of the present invention are:
[0020] A catalyst layer is sprayed on one side of the cation exchange membrane close to the negative electrode to form a membrane electrode. The catalyst layer has a large distribution area and high catalytic efficiency. At the same time, the catalyst layer can also inhibit the serious membrane penetration effect of polysulfides, thereby improving the redox kinetics of polysulfides and the power density of the battery.
[0021] The catalyst of the present invention uses transition metal sulfide supported by graphene, and uses graphene two-dimensional materials as carriers to improve the exposure of active sites in transition metal sulfide, increase the utilization rate of catalysts, and further improve the redox kinetics of polysulfide and the power density of batteries. At the same time, due to the large specific surface area and electronegativity of graphene, the transition metal sulfide nanomaterial supported by graphene sprayed on the cation exchange membrane can block and repel negatively charged polysulfide, inhibit the serious membrane penetration effect of polysulfide, and significantly improve the coulombic efficiency and cyclability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A schematic diagram of a polysulfide flow battery based on a membrane electrode provided in an embodiment of the present invention.
[0024] Figure 2 Power density diagram of polysulfide flow battery based on membrane electrode provided for embodiments of the present invention and comparative examples.
[0025] Figure 3 The polysulfide flow battery based on the membrane electrode provided in the embodiments of the present invention and the comparative examples is 20 mA / cm 2 Coulombic efficiency plot for 100 cycles at different current densities. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] In the description of the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0028] The embodiment of the present invention provides a polysulfide flow battery based on a membrane electrode, wherein a first catalyst layer is scraped on the negative electrode of the battery, and a second catalyst layer is sprayed on the side of the cation exchange membrane of the battery close to the negative electrode. Spraying the catalyst layer on the cation exchange membrane to form a membrane electrode can increase the distribution area of the catalyst and improve the catalytic efficiency of the catalyst. At the same time, the catalyst layer can also prevent polysulfides from penetrating the membrane, thereby improving the redox kinetics of polysulfides and the power density of the battery.
[0029] As a further improvement, the catalyst material of the first catalyst layer and the second catalyst layer is a transition metal sulfide or a transition metal-nitrogen-carbon material supported by graphene, but is not limited thereto. Preferably, the transition metal sulfide supported by graphene is selected from CoS x @rGO、CuS x @rGO、Ni3S4@rGO、Ni 1-x Co x S2@rGO、Ni 3-x Co xOne or more of S4@rGO. The transition metal-nitrogen-carbon material is selected from one or more of Fe-NC, Co-NC, and Ni-NC. Further preferably, the catalyst material of the first catalyst layer and the second catalyst layer is selected from the graphene-supported transition metal sulfide. The embodiment of the present invention uses graphene-supported transition metal sulfide, which, on the one hand, serves as a two-dimensional carrier of transition metal sulfide, improves the exposure of active sites in transition metal sulfide, increases the utilization rate of catalyst, and further improves the redox kinetics of polysulfide and the power density of battery; on the other hand, due to the large specific surface area and electronegativity of graphene, the graphene-supported transition metal sulfide nanomaterial sprayed on the cation exchange membrane can block and repel negatively charged polysulfide, inhibit the serious membrane penetration effect of polysulfide, and significantly improve the coulombic efficiency and cyclability of the battery.
[0030] As a further improvement, the preparation method of the graphene-supported transition metal sulfide is as follows: ultrasonically dispersing graphene oxide in a solvent, adding a sulfur source and a transition metal nitrate, stirring evenly, heating at 120-200°C for 8-24 hours in a hydrothermal reactor, cooling, and washing several times to obtain the product, i.e., the graphene-supported transition metal sulfide. The sulfur source is selected from one of thiourea, thioacetamide, and sodium thiosulfate; the transition metal nitrate is selected from one of nickel nitrate, cobalt nitrate, and copper nitrate. The concentration of the graphene oxide solution is 1 mg / ml, the mass ratio of graphene oxide to transition metal nitrate is 1:5-1:20, and the mass ratio of transition metal nitrate to sulfur source is 1:5-1:20.
[0031] As a further improvement, the solvent used to dissolve graphene oxide is one of water, ethylene glycol, glycerol and the like.
[0032] As a further improvement, the catalyst loading of the first catalyst layer is 2-30 mg / cm 2 , preferably 5 mg / cm 2 、10mg / cm 2 、15mg / cm 2 、18mg / cm 2 The catalyst loading of the second catalyst layer is 1-20 mg / cm 2 , preferably 2 mg / cm 2 , 5mg / cm 2 , 9mg / cm 2 , 12mg / cm 2 、15mg / cm 2 、18mg / cm 2 .
[0033] As a further improvement, the positive and negative electrodes are made of carbon felt or carbon paper.
[0034] As a further improvement, the cation exchange membrane is selected from one of Nafion N212, N115 or N117. Such cation exchange membranes have stronger cation conductivity than traditional ceramic diaphragms, and the internal resistance of the battery is small, so that the power density and energy efficiency are high.
[0035] As a further improvement, the negative electrode active material is one of Na2S2 or Na2S4, with a concentration of 0.1-7 mol / L.
[0036] As a further improvement, the positive electrode active material is I-, Na4[Fe(CN)6], Mn 2+ , TEMPO, ferrocene, Pb 2+ 、Ce 3+ etc. and one of its derivatives, with a concentration of 0.5-8 mol / L.
[0037] The embodiment of the present invention further provides a method for assembling the above-mentioned polysulfide flow battery based on membrane electrode, comprising the following steps:
[0038] S1, preparing the catalyst material into a scraping slurry, and scraping it on the surface of the negative electrode;
[0039] S2, preparing the catalyst material into a spray slurry, and spraying it on the surface of the cation exchange membrane;
[0040] S3, assembling the polysulfide flow battery according to conventional methods, ensuring that the side of the cation exchange membrane sprayed with the catalyst faces the negative electrode.
[0041] As a further improvement, the catalyst material is prepared into a scraping slurry or a spraying slurry by uniformly dispersing the catalyst material in an organic solvent A, dissolving a binder in an organic solvent B, mixing the two solutions, and ultrasonically dispersing to obtain a scraping slurry or a spraying slurry. Preferably, the organic solvent A is one or a mixed solvent of ethanol, isopropanol or n-propanol. Preferably, the organic solvent B is one or a mixed solvent of N,N-dimethylformamide or N-methylpyrrolidone, etc. Preferably, the binder is a mixture of one or more organic polymers such as PVDF, PTFE, and Nafion. This solvent and binder can form a scraping slurry or a spraying slurry with good performance. The scraping slurry has good adhesion, which is convenient for forming a uniform scraping layer, and the spraying slurry does not clog the spraying machine.
[0042] As a further improvement, the mass ratio of the catalyst material to the binder is 20:1-2:1, preferably 20:1, 18:1, 15:1, 10:1, 5:1. The volume ratio of the organic solvent A to the organic solvent B in the scraping slurry and the spraying slurry is 50:1-10:1, preferably 50:1, 40:1, 30:1, 20:1.
[0043] As a further improvement, the sprayed cation exchange membrane is hot pressed at 80°C-200°C and 0.1-10MPa for 1-20min, so that the catalyst layer is more firmly attached to the cation exchange membrane, thereby improving the stability of the liquid flow battery.
[0044] As a further improvement, the process of scraping or spraying is accompanied by a drying process at 45-120° C. to accelerate the volatilization of the solvent.
[0045] Example 1
[0046] Refer to the attached Figure 1 As shown, a polysulfide liquid flow battery based on a membrane electrode includes a battery body, a positive electrode storage tank and a negative electrode storage tank.
[0047] The battery body includes a cation exchange membrane that divides the battery body into left and right chambers, a negative electrode, and a positive electrode. The surface of the cation exchange membrane close to the negative electrode is sprayed with a catalyst layer. The negative electrode is also loaded with a catalyst layer.
[0048] The negative electrode storage tank is connected to the negative electrode chamber of the battery body through a pump and a pipeline, and is used for storing the polysulfide negative electrode solution.
[0049] The positive electrode storage tank is connected to the positive electrode chamber of the battery body through a pump and a pipeline, and is used for storing the positive electrode solution.
[0050] Graphene-supported Ni2CoS4 (Ni2CoS4@rGO) was used as the catalyst, 4 cm 2 The carbon felt was used as the positive electrode, and a 4 cm thick layer of catalyst was scraped off. 2 The carbon felt is used as the negative electrode, and the N115 membrane with a single-sided sprayed catalyst is used as the cation exchange membrane. The catalyst loading on the negative electrode carbon felt is 18 mg / cm 2 The catalyst loading on the surface of the sprayed cation exchange membrane is 9 mg / cm 2 The positive electrode active material is 10mL 0.5M Na4[Fe(CN)6] solution. The negative electrode active material is 6mL 1M Na2S2 solution. The N115 membrane sprayed with the catalyst layer faces the negative electrode and is assembled into a liquid flow battery according to conventional methods.
[0051] The preparation method of Ni2CoS4@rGO is as follows: graphene oxide is ultrasonically dispersed and dissolved in a solvent, thiourea and cobalt nitrate are added, and stirred evenly. In a hydrothermal reactor, it is heated at 180°C for 20 hours, cooled, and washed several times to obtain the product. The concentration of the graphene oxide solution is 1 mg / ml, the mass ratio of graphene oxide to cobalt nitrate is 1:10, and the mass ratio of cobalt nitrate to sulfur source is 1:15. The solvent used to dissolve graphene oxide is ethylene glycol.
[0052] The preparation method of the scraping slurry and the spraying slurry is as follows: the catalyst material is uniformly dispersed in the organic solvent A, the binder is dissolved in the organic solvent B, the two solutions are mixed, and ultrasonic dispersion is performed to obtain the scraping slurry or the spraying slurry. The organic solvent A is ethanol. The organic solvent B is N, N-dimethylformamide. The binder is PVDF. The mass ratio of the catalyst material to the binder is 10:1. The volume ratio of the organic solvent A to the organic solvent B in the scraping slurry and the spraying slurry is 30:1.
[0053] The sprayed ion exchange membrane was hot pressed at 150°C and 8MPa for 10min.
[0054] The process of scraping or spraying is accompanied by a drying process at 90° C. to accelerate the volatilization of the solvent.
[0055] The positive and negative active materials were pumped into the positive and negative electrodes respectively, and the battery was charged and discharged at constant current at different current densities. 2 A 100-cycle long cycle performance test was performed, and the coulombic efficiency under long cycle was obtained from the charge and discharge capacity ratio.
[0056] Example 2
[0057] The transition metal-nitrogen-carbon material Fe-NC is used as the catalyst, and the other steps are the same as those in Example 1.
[0058] Comparative Example 1
[0059] Ni2CoS4 was used as the catalyst without graphene loading, and the rest was the same as in Example 1.
[0060] Comparative Example 2
[0061] No catalyst was sprayed on the cation exchange membrane N115 (blank control without membrane electrode), and the rest was the same as in Example 1.
[0062] Comparative Example 3
[0063] No catalyst was used (blank control), and the rest was the same as in Example 1.
[0064] The power density test data of the flow batteries of Examples 1 to 2 and Comparative Examples 1 and 3 are as follows: Figure 2 shown.
[0065] Depend on Figure 2 It can be seen that the power density of the flow battery of Example 1 and Example 2 is significantly higher than that of Comparative Example 1 and Comparative Example 3, indicating that the use of graphene-loaded Ni2CoS4 as a catalyst can significantly improve the catalytic efficiency of the catalyst, thereby improving the power density of the flow battery. Analysis of the reasons believes that graphene can increase the exposure of active sites in transition metal sulfides, thereby increasing the utilization of the catalyst. The power density of the flow battery of Example 2 is significantly higher than that of Comparative Example 1 and Comparative Example 3, indicating that Fe-NC is a catalyst coated on the negative electrode side of the cation exchange membrane, which can significantly improve the power density of the flow battery. Analysis of the reasons believes that Fe-NC is a catalyst coated on the negative electrode side of the cation exchange membrane, the distribution area of the catalyst layer is large, the catalytic efficiency is high, and the catalyst layer can also suppress the serious membrane penetration effect of polysulfides, thereby improving the redox kinetics of polysulfides and the power density of the battery.
[0066] The coulombic efficiency of the flow batteries of Example 1 and Comparative Example 2 is as follows: Figure 3 shown.
[0067] Depend on Figure 3 It can be seen that the coulombic efficiency and the number of cycles of the flow battery of Example 1 are significantly higher than those of Comparative Example 2, indicating that the catalyst layer is sprayed on one side of the cation exchange membrane close to the negative electrode, which can significantly improve the coulombic efficiency and the number of cycles of the flow battery. Analysis of the reasons shows that the catalyst layer is sprayed on one side of the cation exchange membrane close to the negative electrode, and the catalyst distribution area is large, which improves the catalytic efficiency. At the same time, the catalyst layer can also prevent the membrane penetration effect of polysulfides.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A polysulfide flow battery based on a membrane electrode, characterized in that: A first catalyst layer is scraped on the negative electrode of the battery, and a second catalyst layer is sprayed on one side of the cation exchange membrane of the battery close to the negative electrode; the catalyst materials of the first catalyst layer and the second catalyst layer are transition metal sulfides supported by graphene; the transition metal sulfides supported by graphene are selected from CoSx@rGO, CuSx@rGO, Ni3S4@rGO, Ni 1-x CoxS2@rGO、Ni 3-x One or more of CoxS4@rGO; the catalyst loading of the first catalyst layer is 2-30 mg / cm 2 The catalyst loading of the second catalyst layer is 1-20 mg / cm 2 ; The positive electrode active material of the battery is I - 、Na4[Fe(CN)6]、Mn 2+ , TEMPO, ferrocene, Pb 2+ 、Ce 3 + One of its derivatives, at a concentration of 0.5-8 mol / L.
2. A method for assembling a polysulfide flow battery based on a membrane electrode according to claim 1, characterized in that: The following steps are involved: S1, preparing the catalyst material into a scraping slurry, and scraping it on the surface of the negative electrode; S2, preparing the catalyst material into a spray slurry, and spraying it on the surface of the cation exchange membrane; S3, assembling the polysulfide flow battery, ensuring that the side of the cation exchange membrane sprayed with the catalyst faces the negative electrode; The catalyst material is a graphene-supported transition metal sulfide; the graphene-supported transition metal sulfide is selected from CoSx@rGO, CuSx@rGO, Ni3S4@rGO, Ni 1-x CoxS2@rGO、Ni 3-x One or more of CoxS4@rGO.
3. The method according to claim 2, characterized in that The catalyst material is prepared into a scraping slurry or a spraying slurry by uniformly dispersing the catalyst material in an organic solvent A, dissolving a binder in an organic solvent B, mixing the two solutions, and ultrasonically dispersing to obtain a scraping slurry or a spraying slurry.
4. The method according to claim 3, characterized in that The organic solvent A is selected from one or more of ethanol, isopropanol or n-propanol; the organic solvent B is selected from one or more of N,N-dimethylformamide or N-methylpyrrolidone; the binder is selected from one or more of PVDF, PTFE and Nafion.
5. The method according to claim 4, characterized in that The mass ratio of the catalyst material to the binder is 20:1-2:
1.
6. The method according to claim 2, characterized in that The sprayed cation exchange membrane is hot pressed at 80°C-200°C and 0.1-10 MPa for 1-20 min.
Citation Information
Patent Citations
Doping modification method and application of porous carbon material
CN108172801A
Low-cost neutral flow battery stack
CN111584914A
Nitrogen-doped porous carbon loaded metal cobalt material as well as preparation method and application thereof
CN112259903A
Multifunctional diaphragm of lithium-sulfur battery and preparation method of multifunctional diaphragm
CN112768840A